“Filoviruses”: a real pandemic threat? - Martina, Byron EE (WILEY-VCH Verlag, 2009)
Filoviruses are zoonotic and among the deadliest viruses known to mankind, with mortality rates in outbreaks reaching up to 90%. Despite numerous efforts to identify the host reservoir(s), the transmission cycle of filoviruses between the animal host(s) and humans remains unclear. The last decade has witnessed an increase in filovirus outbreaks with a changing epidemiology. The high mortality rates and lack of effective antiviral drugs or preventive vaccines has propagated the fear that filoviruses may become a real pandemic threat. This article discusses the factors that could influence the possible pandemic potential of filoviruses and elaborates on the prerequisites for the containment of future outbreaks, which would help prevent the evolution of filovirus into more virulent and more transmissible viruses.